Understanding ADHD : A Conversation with Stephen Hinshaw. - Burton, Howard (Toronto : Open Agenda Publishing, 2020)
This book is based on an in-depth, filmed conversation between Howard Burton and Stephen Hinshaw, Professor of Psychology at UC Berkeley. Stephen Hinshaw is an expert in the fields of clinical child and adolescent psychology and developmental psychopathology, as well as stigma, preventive interventions and dehumanization related to mental illness. This extensive conversation examines the facts and misunderstandings surrounding ADHD, diagnosis and misdiagnosis, treatment, family responsibilities, the subtitles of medication, adult ADHD, gender, what's happening on an international level and fin.
Intro -- A Note on the Text -- Introduction -- The Conversation -- I. On Genes and Explorers -- II. Brain Biology -- III. Diagnosis and Treatment -- IV. Behaviour and Medication -- V. Adults and Gender -- VI. Stigma -- VII. Public Policy -- VIII. Adderall for All? -- IX. Global Perspectives -- X. Towards A Better Future? -- Continuing the Conversation
JSTOR
Keywords: Hinshaw, Stephen P. -- Interviews; Hinshaw, Stephen P; Attention-deficit hyperactivity disorder; Minimal brain dysfunction; Attention Deficit Disorder with Hyperactivity; Trouble déficitaire de l'attention.; Dysfonction cérébrale minime; Adolescent; Developmental; PSYCHOLOGY; Attention-Deficit Disorder (ADD-ADHD); Psychopathology; FAMILY & RELATIONSHIPS; Attention-deficit hyperactivity disorder; Electronic books; Interviews